2021
DOI: 10.1186/s12966-021-01174-z
|View full text |Cite
|
Sign up to set email alerts
|

Demographic characteristics associated with circadian rest-activity rhythm patterns: a cross-sectional study

Abstract: Background Rest-activity rhythm (RAR), a manifestation of circadian rhythms, has been associated with morbidity and mortality risk. However, RAR patterns in the general population and specifically the role of demographic characteristics in RAR pattern have not been comprehensively assessed. Therefore, we aimed to describe RAR patterns among non-institutionalized US adults and age, sex, and race/ethnicity variation using accelerometry data from a nationally representative population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 56 publications
6
35
0
Order By: Relevance
“…In a previous study, we found that RAR patterns vary by age and sex ( 28 ). However, our age-stratified results showed that younger and older adults with disrupted RAR are at similar risk of having excess adiposity, implying that age was not an effect modifier of the association with obesity.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a previous study, we found that RAR patterns vary by age and sex ( 28 ). However, our age-stratified results showed that younger and older adults with disrupted RAR are at similar risk of having excess adiposity, implying that age was not an effect modifier of the association with obesity.…”
Section: Discussionmentioning
confidence: 94%
“…Detailed information regarding generation of RAR metrics has been reported elsewhere ( 28 ). In brief, participants were instructed to wear an accelerometer (ActiGraph GT3X+, Pensacola, FL) on their non-dominant wrist for seven consecutive 24-hour periods.…”
Section: Methodsmentioning
confidence: 99%
“…Wrist accelerometers were incorporated in the 2011–2014 NHANES study cycle and this is the first time that 24-hour objective actigraphy data are available on a nationally representative sample of US residents. 22 NHANES used a multistage probability sampling design to produce a weighted, representative sample of the US population. 23 Our sample included adults ≥20 years old who had at least 4 days of validated accelerometer recordings and valid oral glucose tolerance test (OGTT) data from NHANES 2011–2014 cycles (data set 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…These changes are known as biological rhythms and are induced by signals from internal molecular mechanisms. In human beings, sleep-wake activity follows a diurnal pattern which is called the rest–activity rhythm (RAR) ( Li et al, 2021 ). In recent years, a variety of methods recording several days of continuous accelerometer data could be used to detect RAR features ( Smagula et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%